Cesarina Lupati, a writer traveling between two shores - Bravo Herrera , Fernanda Elisa (Revista Melibea, 2023)
This article intends to reconstruct from comparativism the representa- tions and inscriptions linked to wandering, that is, to the displacement between Argentina and Italy in a selection of scattered journalistic texts of the Italian writer Cesarina Lupati (1877-1957). Two experiences are taken into account for this: that of the trip as a protagonist and that of emigration as an observer. In both, a her- meneutic process is recognized that implies a perspective of both phenomena and is outlined as an identity and political configuration. Some of the issues that will be studied are emigration, identity formation, the nationalization process and the construction of the Nation-State, the representations of Argentina and Argentines and relations with Italy and Italian emigrants, the various political commitments and cultural, declined from pedagogy, feminism and pacifism. In this way, it is ex- pected to contribute to the recovery of a rich production, not only for its documen- tary value but also for its literary value, shedding light on the figure of this forgotten marginalized writer.